Debatable Aspects of Progressive Taxation of Individual Incomes in Russia - A. P. Garnov; M. M. Levkevich (Вестник Российского экономического университета имени Г. В. Плеханова, 2021)
The present research deals with debatable aspects connected with introduction of progressive taxation of individual incomes in this country. In spite of the fact that in 2021 an attempt was made to introduce the progressive scale on income tax, different political parties put forward their own approaches substantiating them by demonstrating their regulating impact on economy. It is necessary to realize that progression in taxation involves not only the scale alteration. Today the possibility of progressive tax introduction is being discussed on the background of cutting their number in the fiscal system. In fact such innovations, despite their advantages, could have irrevocable consequences. Among key threats we can mention an increase in the shadow share of economy; administration challenges connected with labour intensity and extra costs; growing capital outflow abroad; general drop in economy competitiveness due to declining entrepreneurial urge towards profit maximization, etc. The article systematizes approaches presented by political parties for discussion and structures the author's approach to introduction of progressive rates based on generalized experience of best practices, adapted to Russian reality. The results of practical testing of authors' vision illustrated by income tax by different rates gives an opportunity to compare the tax burden, which can be estimated in order to enlarge citizens' groups with different levels of incomes.